2014
DOI: 10.14807/ijmp.v5i4.239
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Advanced Planning and Scheduling Systems

Abstract: Currently, the activities of the planning and control of companies are becoming increasingly complex and the managers of this area are constantly pressured to reduce operating costs, maintain inventories at adequate levels, to meet fully the demand of customers, and to respond effectively to the changes that occur. The planning and scheduling task is important for most companies, so according to some authors, there is a need for further analysis of the practical use of production planning and control systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Arsovski et al (2009) stated that APS systems represent the most relevant innovation in planning processes since the introduction of MRP systems in the 1970s. Literature reviews about APS systems can be found in Comelli et al (2008), Tyagi et al (2013), andde Sousa et al (2014).…”
Section: Scheduling Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsovski et al (2009) stated that APS systems represent the most relevant innovation in planning processes since the introduction of MRP systems in the 1970s. Literature reviews about APS systems can be found in Comelli et al (2008), Tyagi et al (2013), andde Sousa et al (2014).…”
Section: Scheduling Ecosystemmentioning
confidence: 99%
“…Zhang and Wong (2018) presented an improved ant colony approach for the IPPS problem, designed to fit the specific characteristics of IPPS. Although the IPPS problem will be the object of Section 4.2, we anticipate that literature reviews about this subject can be found in Maravelias and Sung (2009), Li et al (2010), Phanden et al (2011), de Sousa et al (2014, and Li and Gao (2020d).…”
Section: Scheduling Ecosystemmentioning
confidence: 99%
“…work orders). The PPC system seeks to align the company’s supply with the customers’ demand by maximizing the organizational performance and competitiveness in terms of quality, cost and delivery deadline (Guerra, Silva, & Tondolo, 2014; Sousa, Camparotti, Guerrini, Silva, & Azzolini, 2014).…”
Section: Hybrid Production Systems (Mts–mto)mentioning
confidence: 99%